Using Technology to Build Inclusive Financial Systems - Ivatury, Gautam (World Bank, Washington, DC, 2012)
Innovative use of information and communications technologies to inexpensively process a large volume of small transactions and deliver a wide range of financial services may help to make microfinance institutions (MFIs) more efficient and commercial banks more interested in serving poor people. Falling hardware costs and growing support infrastructure are making these technologies increasingly available. From 1999 to 2004, the number of mobile subscribers in Africa grew from 7.5 million to 76.8 million. Besides reducing delivery costs for banks, poor people may ultimately prefer using these channels because they are inexpensive and convenient. Many who are unbanked now may gain access to financial services for the first time. In a recent CGAP survey, 62 financial institutions in 32 countries report using technology channels, such as automated teller machines (ATMs), point of sale (POS) card readers, and mobile phones, to handle transactions for poor customers. Some are using new technology to better serve existing customers; others hope to reach new clients in areas where setting up a bank branch may be too costly. In Brazil, private-sector banks, such as Banco Bradesco and Lemon Bank, and state-owned banks such as Banco do Brasil and Caixa Economica Federal, have developed about 30,000 so-called 'banking correspondents.' Lottery outlets, post offices, supermarkets, grocery stores, petrol stations, and other retail outlets act as agents for the bank, using POS terminals or PCs to distribute a range of banking services, such as savings, credit, money transfers, insurance, and government benefit distribution. Using this approach, Brazilian banks opened about 10 million new current accounts since 2000.